IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DALAM PEMBELAJARAN MATEMATIKA DI SMPLB TPA JEMBER - Wulandari, Fitri; Susanto, S; Dafik, D (Kadikma, 2012)
Abstract. The aim of the implementation of teaching and learning activities at the Extraordinary School is to achieve the learning objectives. One of the procedures to improve the quality of education is implementing School Based Curriculum (SBC) fully. A data collecting method used in this research are interview, observation, documentation and questioner. The data obtained from interview, observation, documentation and questioner will be analyzed by qualitative descriptive techniques. Based on the result, the propernes of SBC implementation for mathematics learning in SMPLB-A and SMPLB-B shows 67,22% with “Good” category and 82% with “Very Good” category, respectively. In general, the implementation of SBC for mathematics learning at SMPLB has been applied properly but there are some modification done by teachers. Key Words: SBC, Implementation